2018
DOI: 10.5194/tc-2018-98
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Three years of sea ice freeboard, snow depth, and ice thickness of the Weddell Sea from Operation IceBridge and CryoSat-2

Abstract: Abstract. We examine the variability of sea ice freeboard, snow depth, and ice thickness in three years (2011, 2014, and 2016) suggesting a highly variable but broadly thicker ice cover compared to that inferred from drilling and ship-based measurements. Spatially, snow depth and ice thickness are higher in the more deformed ice of the western Weddell. Radar 10 freeboards (uncompensated for snow thickness) from CryoSat-2 (CS-2), sampled along the same transect, are consistently higher (by up to 8 cm) than … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 16 publications
(28 reference statements)
0
11
0
Order By: Relevance
“…Previous ICESat analyses (e.g., Kurtz & Markus, 2012) proceeded by assuming that the snow ice interface was at sea level (all the freeboard is snow) based on ship‐based observations of the ice cover. However, more recent analysis of NASA's Operation IceBridge aerial surveys in the Weddell and Bellingshausen seas has questioned this assumption (Kwok & Kacimi, 2018; Kwok & Maksym, 2014; Petty et al, 2017). More sophisticated snow modeling efforts, combined with these new airborne data sets, are urgently needed.…”
Section: Discussionmentioning
confidence: 99%
“…Previous ICESat analyses (e.g., Kurtz & Markus, 2012) proceeded by assuming that the snow ice interface was at sea level (all the freeboard is snow) based on ship‐based observations of the ice cover. However, more recent analysis of NASA's Operation IceBridge aerial surveys in the Weddell and Bellingshausen seas has questioned this assumption (Kwok & Kacimi, 2018; Kwok & Maksym, 2014; Petty et al, 2017). More sophisticated snow modeling efforts, combined with these new airborne data sets, are urgently needed.…”
Section: Discussionmentioning
confidence: 99%
“…The zero sea-ice freeboard assumption approach assumes that snow depth is equal to the total freeboard (Kurtz and Markus, 2012), which is not always true, particularly for thinner ice with no snow cover at all. This could result in an underestimate of sea-ice thickness (Kwok & Kacimi, 2018; Kern and others, 2016). The empirical equation approach provides a direct conversion of total freeboard into sea-ice thickness, totally based on field measurements.…”
Section: Methodsmentioning
confidence: 99%
“…OIB’s snow thickness measurements from snow radar constituted a major advance as they allowed large‐scale mapping of both first‐year and multi‐year snow and ice thickness over sea ice for the first time. This combination made it possible to monitor sea ice thickness annually across large portions of the western Arctic Ocean (e.g., Farrell et al., 2012; Kurtz et al., 2013; Kurtz & Farrell, 2011; Richter‐Menge & Farrell, 2013), and to produce the first multiyear examination of sea ice cover variability in the Weddell Sea ice cover (Kwok & Kacimi, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The spatial patterns of Arctic snow (total) freeboard mapped by OIB confirmed previous studies: higher freeboards are generally found over the deformed multi‐year sea ice north of Greenland and lower freeboard are found over first‐year ice in the Beaufort and Chukchi seas (Kwok et al., 2012; Richter‐Menge & Farrell, 2013). Antarctic surveys showed higher freeboards in the western Weddell Sea and lower freeboards in the seasonal ice farther from the coasts in both the eastern Weddell and Bellingshausen seas (Kwok & Kacimi, 2018; Kwok & Maksym, 2014; Wang et al., 2016).…”
Section: Discussionmentioning
confidence: 99%